Adaptive robust barrier‐based control of a 3D flexible riser system subject to boundary displacement constraints - Ma, Ge; Tan, Zhifeng; Liu, Yiming; Zhao, Zhijia; Zou, Tao (International journal of robust and nonlinear control, 2022)
This article involves an adaptive robust barrier‐based control of a three‐dimensional riser system subject to system uncertainties and output constraints. A barrier‐based Lyapunov function and a dynamical online update technique are merged to develop new adaptive robust control schemes for dampening the vibration, compensating for parametric uncertainties, and dealing with the constraints in the system. A rigorous Lyapunov analysis is exploited to guarantee the uniformly bounded stability in the controlled system. Finally, the efficacy of the designed approach is validated via simulation results.